2018
DOI: 10.1111/ejed.12253
|View full text |Cite
|
Sign up to set email alerts
|

Innovative approaches to continuous professional development (CPD) in early childhood education and care (ECEC) in Europe: Findings from a comparative review

Abstract: This article explores innovation as an aspect of in-service continuous professional development (CPD) in ECEC. Based on a literature review and a cross-country analysis conducted in ten European countries, we found that innovation in CPD was understood as a way to improving quality in ECEC. CPD no longer solely deals with practitioners' knowledge and skills. Rather, it encompasses processes such as critical thinking, reflexivity and co-creation within and across ECEC systems.Two overall approaches to innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 16 publications
(20 reference statements)
0
24
0
4
Order By: Relevance
“…The lead teacher may contribute to the quality of interactions of all staff either formally, through meetings and planning, or informally, through observation, conversations and role modeling. The importance of informal supervision and teamwork has been recently highlighted as an important component of professional development (Jensen and Iannone 2015). In a recent Dutch study (Slot et al 2015) a range of professional development activities was addressed, including more conventional forms (e.g., in-training service) to less studied ones (e.g.,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lead teacher may contribute to the quality of interactions of all staff either formally, through meetings and planning, or informally, through observation, conversations and role modeling. The importance of informal supervision and teamwork has been recently highlighted as an important component of professional development (Jensen and Iannone 2015). In a recent Dutch study (Slot et al 2015) a range of professional development activities was addressed, including more conventional forms (e.g., in-training service) to less studied ones (e.g.,…”
Section: Discussionmentioning
confidence: 99%
“…Regulated childcare settings for children under 3 years old include centrebased care (i.e., crèche), in private for profit and private non-profit institutions, and home-based care (i.e., family day care), although home-based care is less used. In 2014, places in these formal settings together were available for 49.2% of children Some European projects have highlighted differences and commonalities between countries regarding ECEC systems and curricula (e.g., Gregoriadis et al 2014;Jensen and Iannone 2015) and also regarding teacher education. An analysis of pre-service education in 10 European countries concluded that there is a broad trend to increase demand for university-level qualifications, although substantial differences exist between countries in the study programmes, contents, main principles and practical experiences provided (Jensen and Iannone 2015).…”
Section: Ecec and Caregiver Education In Portugalmentioning
confidence: 99%
See 2 more Smart Citations
“…PD is costly in terms of time and money and it is important to ensure that time spent in PD is worthwhile. Continuous PD is identified as an approach to improving the quality of EC around the world (Jensen and Iannone 2018). As in other countries (Jensen and Iannone 2018; OECD 2012), both state and federal PD policies in the US, for example, specify a required number of hours to be completed annually.…”
Section: Ongoing and Intensive Experiencesmentioning
confidence: 99%